2017
DOI: 10.4314/mmj.v29i1.7
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of antibody to hepatitis B core antigen among hepatitis B surface antigen-negative blood donors in Ilorin, Nigeria: A cross-sectional study

Abstract: BackgroundPost-transfusion hepatitis occurs even with stringent donor selection criteria and screening for hepatitis B surface antigen (HBsAg). The objective of this study was to determine the prevalence of antibody to hepatitis B core antigen (anti-HBc) in HBsAg-negative blood donors. MethodsThis was a cross-sectional study in which 200 HBsAg-negative blood donors were recruited. Screening for viral markers was done using both a rapid test kit and enzyme-linked immunosorbent assay (ELISA) for anti-HBc IgM. Qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 33 publications
(23 reference statements)
2
10
1
Order By: Relevance
“…Therefore, stringent blood donor screening criteria using a standard questionnaire that provides confidentiality for donors in addition to educational materials to eliminate donors who had ever used recreational drugs may significantly reduce HBV-positive donors irrespective of whether they are voluntary or replacement blood donors. Comparing this study with other studies that investigated total anti-HBc in Nigeria, the prevalence of 48.5% is higher than 32.5% by Ogunfemi et al in Ilorin, 24 but lower than 60.7% and 90.0% from the studies by Akinbami et al in Lagos 18 and Ojo et al in Ife. 25 The 90.0% prevalence was reported pre-HBV vaccination.…”
Section: Discussionsupporting
confidence: 54%
“…Therefore, stringent blood donor screening criteria using a standard questionnaire that provides confidentiality for donors in addition to educational materials to eliminate donors who had ever used recreational drugs may significantly reduce HBV-positive donors irrespective of whether they are voluntary or replacement blood donors. Comparing this study with other studies that investigated total anti-HBc in Nigeria, the prevalence of 48.5% is higher than 32.5% by Ogunfemi et al in Ilorin, 24 but lower than 60.7% and 90.0% from the studies by Akinbami et al in Lagos 18 and Ojo et al in Ife. 25 The 90.0% prevalence was reported pre-HBV vaccination.…”
Section: Discussionsupporting
confidence: 54%
“…The prevalence of HBsAg was 3.5% (7 cases) and HBsAg negative cases were 193, total anti-HBc 10.9% (22 cases), anti-HBc IgM 5.7% (11 cases) and anti-HBs 3% (6 cases). All the 6 anti-HBs positive donors were also found to be positive for total anti HBc indicating past infection, but the result of anti-HBc IgM indicates recent infection [21]. An Indian study support the above results, 12232 healthy blood donors negative for HBsAg were screened for anti-HBc IgM, this study revealed a percentage of (0.12%) reactive for anti-HBc (IgM).…”
Section: Discussionsupporting
confidence: 65%
“…A lower prevalence of total HBcAb was founded in low-prevalence countries such as Iran, France, and Spain (4.9%, 7.3%, and 8.2%, respectively) [16][17][18]. In contrast, a higher prevalence was found in high-prevalence countries like Nigeria, Togo, and Mauritania (32%, 53.9%, and 76.5%, respectively) [19][20][21].…”
Section: Discussionmentioning
confidence: 99%